Enhancing reflective practice in pharmacy education: a pharmacoepidemiology and public health approach / Zakiah Mohd Noordin ... [et al.] - Mohd Noordin, Zakiah; Karuppanan, Mahmathi; Ismail, Farhana Fakhira; Abdul Halim Zaki, Izzati (Faculty of Pharmacy, 2024)
Reflective practice is an integral part of the pharmacy curriculum. It supports development of skills in decision-making, critical thinking, problem-solving, and is important for continuing professional development and ongoing professional practice. At the heart of reflective practice lies the encouragement of learning from both personal experiences and the experiences of others. This strategy not only bridges the gap between academic knowledge and real-world application, but it also encourages communication and collaboration across diverse teams, which are essential components of modern pharmacy practice.